CMOS digitally controlled current follower and its application - Prasertsom, Danucha; Tangsrirat, Worapong (My University, 2009)
A realization of the CMOS digitally controlled current follower (DC-CF) suitable for low-voltage high-frequency application is proposed. To achieve very low input resistance, it is realized using a modification of a low-input resistance stage as an input stage. To achieve the precise digital control of the current gain, the current division technique is used. The proposed DC-CF can operate with low voltage supplies of ±1.5 V, and is designed with 0.5- μm CMOS SCN05H process. As an application, the digitally programmable current-mode universal filter using the proposed DC-CF is given. Simulation results are also included.
Keywords: Current Follower (CF); Current-mode circuits; Digitally programmable